2015
DOI: 10.1017/s1474746415000111
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Relationship between Parenting and Poverty: Theory, Evidence and Policy

Abstract: This is an Accepted Manuscript of an article published by CAMBRIDGE UNIVERSITY PRESS in SOCIAL POLICY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 88 publications
2
22
0
3
Order By: Relevance
“…In addition to the material disadvantages of living in low-income households, participants reflected that low-income parents are more likely to experience non-material disadvantages which can disrupt the ability to parent such as relationship difficulties. These findings are in line with other studies on parenting in poverty (La Placa & Corlyon, 2016) and demonstrates the need for additional support for families during the school holidays.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to the material disadvantages of living in low-income households, participants reflected that low-income parents are more likely to experience non-material disadvantages which can disrupt the ability to parent such as relationship difficulties. These findings are in line with other studies on parenting in poverty (La Placa & Corlyon, 2016) and demonstrates the need for additional support for families during the school holidays.…”
Section: Discussionsupporting
confidence: 92%
“…Given the increased financial pressures, participants identified that low-income households are at risk of experiencing food insecurity during the school holidays and there is a need to support families against this risk. Stakeholders identified that parents were "struggling" during the school holidays as a result of the stress of financial hardships and therefore, the ability to parent is made increasingly difficult (La Placa & Corlyon, 2016). In addition to the material disadvantages of living in low-income households, participants reflected that low-income parents are more likely to experience non-material disadvantages which can disrupt the ability to parent such as relationship difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…We know that children with large amounts of cultural capital tend to do well in the education system, and family practices and attitudes towards education vary between families with various levels of cultural capital (Bourdieu & Passeron, 1977;Lareau, 1987Lareau, , 2011Aarseth, 2017). We also know that lower income is associated with less parental involvement in school (see La Placa & Corlyon, 2016 for an overview). Less is known about the relative weight of cultural and economic capital in association with parental involvement in school.…”
Section: Introductionmentioning
confidence: 99%
“…From a socioecological view of resilience (Ungar, Connelly, Liebenberg, & Theron, 2017), the onus falls on adults in the environment to provide the child with access to protective resources to to buffer risk. In communities characterised by poverty and adversity, many parents and adults are not able to provide such support (La Placa & Corlyon, 2016), and may even contribute to the risk factors facing the child (Flouri, Midouhas, Joshi, & Tzavidis, 2015). Although the expectation that the teacher provides psychosocial support to children deemed to be at risk is contested in literature (Campbell et al 2016), for these children, teachers are often the only adults available who could do so.…”
Section: Introductionmentioning
confidence: 99%